Fostering a Vibrant Music Club Culture: Strategies for Enhancing Student Engagement and Participation in Chinese High School Music Societies (Journal of Interdisciplinary Insights, 2024)
This study investigates strategies for enhancing student engagement and participation in high school music clubs in China. Utilizing a quantitative approach, data was collected through questionnaires from 90 students across three high schools. The study explored demographic profiles, levels of engagement, and factors influencing participation. The results indicated that intrinsic interest in music, quality of club leadership, peer influence, parental support, and school support were significant factors driving engagement. Comparative analysis revealed no significant differences in engagement levels among the schools, suggesting the applicability of these findings across different educational settings. The study concludes that fostering a vibrant music club culture requires a comprehensive approach that includes strong leadership, supportive communities, parental involvement, adequate resources, and integration with academic schedules.